Seroprevalence of SARS-CoV-2 antibodies among oral health care workers with natural seroconversion: a systematic review and meta-analysis - Elisabeth Santigli; Marlene Lindner; Harald H. Kessler; Norbert Jakse; Omid Fakheran (Scientific Reports, 2025)
Abstract Aerosol and droplet exposure makes oral health care workers (OHCWs) highly susceptible to transmissible infections, for example with SARS-CoV-2. Population-based screening is useful in understanding public health interventions in COVID-19. This systematic review with meta-analysis presents the prevalence of SARS-CoV-2 antibodies among OHCWs. An electronic search has been performed to identify records indexed in Medline, Web of Science, Scopus, and the Cochrane Library until December 2023. All observational studies providing data on SARS-CoV-2 antibodies in OHCWs with natural seroconversion were included. The quality of 722 records was evaluated using the Joana Brigg’s Institute (JBI) critical appraisal tool. Finally, ten studies were considered as eligible encompassing point-seroprevalence data on 6,083 dental professionals (dentists, assistants, and administrative staff) from seven European countries and Brazil. The antibody seroprevalence was pooled by a meta-analysis performed with MedCalc® statistical software. Applying random effects model, the overall seroprevalence of immunoglobulin G antibodies among OHCWs was estimated at 13.49% (95% CI 9.15–18.52%). The data indicate a somewhat increased occupation-specific risk for COVID-19 but more studies are required, especially later in the pandemic and following vaccination.